The use of e-voting as a new tool of e-participation in modern democracies - Musiał-Karg, Magdalena (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2014)
Finding the answer to the question of the role of electronic voting in a modern country constitutes an important part of researches into electronic democracy. The recent dynamic development of information and communication technologies (ICT) and mass media have been leading to noticeable changes in functioning of contemporary countries and societies. ICT is beginning to play a greater and greater role and filter down to almost every field of contemporary human life – including politics. Electronic voting represents one of the more and more popular forms of so called e-democracy, and is an interesting research subject in the context of mechanisms for implementing this form of participation in elections, its legitimization, specific technological solutions for e-voting and their effectiveness as well as unintended consequences. The main subject of this text is the use of electronic voting (e-voting) as one of the forms of electronic democracy. The article attempts to answer the following research questions: First, what is the impact of ICT on the political processes – particularly on the voting procedures? Secondly, what is the essence of electronic voting and what are its main features? Finally, what are the e-voting experiences in the European countries? The text is devoted rather to general remarks on e-voting, and does not constitute a complete analysis of the issue. It is intended to be a contribution to the further considerations.

Znalezienie odpowiedzi na pytanie o rolę elektronicznego głosowania w elekcjach państwowych stanowi ważną część badań nad demokracją elektroniczną. W wyniku dynamicznego rozwoju technologii informacyjnych i komunikacyjnych (ICT) doszło do zauważalnych zmian w funkcjonowaniu współczesnych państw i społeczeństw. ICT zaczynają odgrywać większą rolę, przenikając niemal każdą dziedzinę życia współczesnego człowieka – także politykę. Elektroniczne głosowanie stanowi jedną z coraz bardziej popularnych form tzw. e-demokracji, i staje się interesującym przedmiotem badań. Głównym zagadnieniem niniejszego tekstu jest wykorzystanie głosowania elektronicznego (e-głosowania) jako jednej z form demokracji elektronicznej. Artykuł stanowi próbę odpowiedzi na następujące pytania badawcze: po pierwsze, jak ICT wpływają na procesy polityczne – szczególnie na procedury głosowania? Po drugie, co jest istotą głosowania elektronicznego i jakie są jego główne cechy? Wreszcie, jakie doświadczenia z e-głosowaniem mają państwa europejskie? Tekst nie stanowi wyczerpującej analizy przedmiotu badań. Ma być raczej przyczynkiem do dalszych rozważań nad e-demokracją, e-partycypacją, a przede wszystkim e-głosowaniem.
Zastosowanie e-głosowania jako nowego narzędzia e-partycypacji we współczesnej demokracji
Keywords: e-voting; electronic voting; e-democracy; ICT; e-głosowania; głosowanie elektroniczne; e-demokracja; TIK